Choosing a crowdfunding model considering strategic customer behaviour. (19th May 2022) - Xu, Shengshuo; Zhang, Zihao
Abstract : Initial creators can launch reward-based crowdfunding projects using either of two models: All-Or-Nothing (AON) and Keep-It-All (KIA). Under AON, creators receive nothing unless the funding target is achieved. Under KIA, creators keep the entire amount raised, regardless of whether the funding target is achieved. Therefore, under AON, customers will obtain high-quality products if the funding target is achieved, and otherwise, obtain nothing. Under KIA, high-quality products are produced if the goal is met and otherwise, the results are scaled-down products whose quality depends on the amount of funding raised. We build a two-stage model in which two customers (representing informed and uninformed customers) sequentially make their decisions in the two stages. This paper focuses on the opportunity cost borne by the informed customer who pledges in the first stage and we analyse how his strategic behaviour affects the creator's model selection. Our analysis shows that when the fixed cost is large, the AON model has a higher success rate and is more profitable than the KIA model. By analysing the expected profit, success rate and risk by numerical study, we show that (1) when the fixed cost is small, KIA is more profitable than AON. (2) The success rate using the AON model is always higher than that using the KIA model. (3) The risk under AON is higher than under KIA in most cases.